Income inequality in education, and children's schooling attainment in Brazil - Ricardo Paes de Barros; David Lam (Institute for Applied Economic Research (ipea), 2015)
This paper analyzes the determinants of schooling attainment at the household level for 14-years-old in urban regions of Sa\~o Paulo and Northeast Brazil, using data from the 1982 PNAD. We find mean schooling of 4.75 years in Sa\~o Paulo, and 3.25 years in the Northeast, both far short of the seven years of schooling that should have been completed by 14-years-old. In attempting to explain the 1.5 year advantage in the schooling attainment of 14-year-olds in Sa\~o Paulo, we find regional differences in the characteristics of parents that are consistent with the regional difference in child outcomes. Parents' schooling and income are considerably higher in Sa\~o Paulo, and inequality in parental schooling is higher in the Northeast. Regression estimates imply substantial positive effects of parental schooling and income on child schooling attainment. [...]
Keywords: 330